2012
DOI: 10.1111/j.1742-6723.2012.01533.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of working consecutive night shifts on sleep time, prior wakefulness, perceived levels of fatigue and performance on a psychometric test in emergency registrars

Abstract: Registrars sleep a similar amount of time surrounding night and day shifts. Despite reporting the highest levels of fatigue at the end of a night shift, there is no significant difference in reaction times at the end of night shift compared with the beginning of day shift. This correlates with the finding that at the end of night shift the registrars have been awake for less than 16 h, which is the point at which psychomotor performance is expected to decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The after-hours presentation is a risk factor for patients with acute conditions such as stroke, traumatic brain injury, pulmonary embolism, myocardial infarction, cardiac arrest, and ruptured an aortic aneurysm. [293031323334] The factors speculated to increase the mortality in our study may be: reduction in staffing levels during off hours,[35] impairment in performance in emergency settings due to fatigue,[3637] disrupted circadian rhythms, and increased medical errors and complications. [3839] More research is needed to determine the contribution of each on mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The after-hours presentation is a risk factor for patients with acute conditions such as stroke, traumatic brain injury, pulmonary embolism, myocardial infarction, cardiac arrest, and ruptured an aortic aneurysm. [293031323334] The factors speculated to increase the mortality in our study may be: reduction in staffing levels during off hours,[35] impairment in performance in emergency settings due to fatigue,[3637] disrupted circadian rhythms, and increased medical errors and complications. [3839] More research is needed to determine the contribution of each on mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Even so, it is known that the effects of sleeplessness make it hard for one to handle various activities when he or she is awake. 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…conducted on a group of 11 emergency physicians showed no significant differences in reaction times at the end of a night shift compared with the beginning of a day shift. 15 Machi et al 16 evaluated cognition in 13 emergency physicians before and after day and overnight shifts. They showed that short-term memory appears to decline similarly after day and overnight shifts, whereas another study showed that the performance of psychometric tests was not altered after a work shift of 16 hours.…”
Section: How This Is Relevant To Clinical Practicementioning
confidence: 99%